Revitalization of Letjend Suprapto Street Kota Lama Semarang Area as “Little Netherlands” Through Landscape Elements - Adita riska probowati; Hinijati Widjaja; Titiek P. Debora (Universitas Trisakti, 2022)
Kota Lama Semarang is one of the cultural heritage sites that maintains its building facade as a characteristic. However, the arrangement of landscape elements in the street is not in accordance with the principles of cultural heritage. Especially on Letjend Suprapto Street, where the street became the center of activity also the main traffic in the Kota Lama Semarang area. The purpose of this study is to find out wich landscape elements were used in the past that can be applied to current conditions to restore the image of being “Little Netherlands”. The method used is qualitative descriptive method with data acquisition through interviews. The result is to find out what kind of landscape elements used in ancient times as recommendations in designing the street.